Phonetic and phonological imitation of intonation in two varieties of Italian - D’Imperio, Mariapaola; Cavone, Rossana; Petrone, Caterina (Frontiers in Psychology, 2014)
The aim of this study was to test whether both phonetic and phonological representations of intonation can be rapidly modified when imitating utterances belonging to a different regional variety of the same language. Our main hypothesis was that tonal alignment, just as other phonetic features of speech, would be rapidly modified by Italian speakers when imitating pitch accents of a different (Southern) variety of Italian. In particular, we tested whether Bari Italian speakers would produce later peaks for their native rising L+H* (question pitch accent) in the process of imitating Neapolitan Italian rising L*+H accents. Also, we tested whether BI speakers are able to modify other phonetic properties (pitch level) as well as phonological characteristics (changes in tonal composition) of the same contour. In a follow-up study, we tested if the reverse was also true, i.e. whether NI speakers would produce earlier peaks within the L*+H accent in the process of imitating the L+H* of BI questions, despite the presence of a contrast between two rising accents in this variety. Our results show that phonetic detail of tonal alignment can be successfully modified by both BI and NI speakers when imitating a model speaker of the other variety. The hypothesis of a selective imitation process preventing alignment modifications in NI was hence not supported. Moreover the effect was significantly stronger for low frequency words. Participants were also able to imitate other phonetic cues, in that they modified global utterance pitch level. Concerning phonological convergence, speakers modified the tonal specification of the edge tones in order to resemble that of the other variety by either suppressing or increasing the presence of a final H%. Hence, our data show that intonation imitation leads to fast modification of both phonetic and phonological intonation representations including detail of tonal alignment and pitch scaling.